AUTOGENOUS SHRINKAGE OF COMPOSITES BASED ON PORTLAND CEMENT - Vendula Davidová; Pavel Reiterman (Acta Polytechnica CTU Proceedings, 2019)
Autogenous shrinkage of cement based composites is important property influencing number of their engineering application. Its ultimate value is predominantly determined by mineralogical composition of cement and its particle size distribution. Present paper introduces experimental study focused on the evaluation of various cements of grade CEM I 42.5 produced in Czech Republic in terms of shrinkage under autogenous conditions. Selected cement type is currently the most frequently used cement. Conducted study confirmed essential differences in ultimate values of shrinkage, which is partially determined by its specific surface area. Accompanying tests of mechanical properties indicate the influence of particle size distribution, which controls initial phases of cement hydration.